Structural health monitoring of biocomposites, fibre-ieinforced composites and hybrid composites - Jawaid, Mohammad; Thariq, Mohamed; Saba, Naheed (Woodhead Publishing series in composites science and engineering., 2019)
Structural Health Monitoring of Biocomposites, Fibre-Reinforced Composites and Hybrid Composites provides detailed information on failure analysis, mechanical and physical properties, structural health monitoring, durability and life prediction, modelling of damage processes of natural fiber, synthetic fibers, and natural/natural, and natural/synthetic fiber hybrid composites. It provides a comprehensive review of both established and promising new technologies currently under development in the emerging area of structural health monitoring in aerospace, construction and automotive structures. In addition, it describes SHM methods and sensors related to specific composites and how advantages and limitations of various sensors and methods can help make informed choices. Written by leading experts in the field, and covering composite materials developed from different natural fibers and their hybridization with synthetic fibers, the book's chapters provide cutting-edge, up-to-date research on the characterization, analysis and modelling of composite materials.